Escherichia coli O157:H7 and Salmonella Typhimurium inactivation by the effect of mandarin, lemon, and orange by-products in reference medium and in oat-fruit juice mixed beverage. (March 2016) - Sanz-Puig, Maria; Pina-Pérez, M.Consuelo; Martínez-López, Antonio; Rodrigo, Dolores
Abstract: The antimicrobial capability of three water extracts of citrus peels was evaluated against Salmonella enterica serovar Typhimurium and Escherichia coli O157:H7 at various concentrations (0.5, 1, 5, 10%) and temperatures (5, 10, 22 °C) in a reference medium. The best of them was mandarin by-product, achieving a maximum inactivation level against S. Typhimurium (8 log10 cycles) with 5% at 5 °C. Also, this by-product had the highest total polyphenol content. Mandarin by-product showed a bactericidal effect in a food matrix also at 5 °C (≈2 log10 cycles). All results were adjusted to the Weibull model and the b values indicated that the higher concentration of mandarin, the greater the inactivation rate in reference medium, without significant differences between 5 and 10%. Similarly, in the food matrix, the inactivation rate of S . Typhimurium was higher when the mandarin by-product was added. Therefore, the mandarin by-product could be used as a control measure of S . Typhimurium in pasteurized products, which are stored under refrigeration. Highlights: The antimicrobial activity of mandarin, orange, and lemon by-products was assessed. Mandarin had the most bactericidal effect in reference medium. The maximum inactivation level of mandarin was 8 log cycles against Salmonella Typhimurium. The mandarin antimicrobial effect was lower in food matrix than in reference medium. Higher mandarin by-product addition produced greater microorganism inactivation.